2014
DOI: 10.2478/s11696-014-0596-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth and morphological studies of NiO/CuO/ZnO based nanostructured thin films for photovoltaic applications

Abstract: At present, inorganic semiconducting materials are the most economical and viable source for the renewable energy industry. The present work deals with the morphological and optical characterization of copper oxide (CuO) and zinc oxide (ZnO) thin films fabricated by layer by layer deposition on nickel oxide (NiO) coated indium tin oxide (ITO) glass by solution processing methods, mainly chemical bath deposition (CBD) and hydrothermal deposition (HTD) processes at room temperature. As a whole, the above inorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…The production of copper and zinc nanocomposite with controllable sizes, shapes and surface properties is vital for exploring copper-zinc-based nano-oxides for different applications. There are numerous reports on chemically and physically prepared nanocrystalline copper-zinc based oxides [1, 10, 15, 20]. Deraz et al reported the synthesis and characterisation of new copper-based nanocomposite using glycine-assisted combustion method [7] while in his paper (Habibi et al) [21] fabricated and characterised ternary CuO-ZnO-Cu 2 O nanocomposites by Sol-Gel Route at different temperatures [22].…”
Section: Introductionmentioning
confidence: 99%
“…The production of copper and zinc nanocomposite with controllable sizes, shapes and surface properties is vital for exploring copper-zinc-based nano-oxides for different applications. There are numerous reports on chemically and physically prepared nanocrystalline copper-zinc based oxides [1, 10, 15, 20]. Deraz et al reported the synthesis and characterisation of new copper-based nanocomposite using glycine-assisted combustion method [7] while in his paper (Habibi et al) [21] fabricated and characterised ternary CuO-ZnO-Cu 2 O nanocomposites by Sol-Gel Route at different temperatures [22].…”
Section: Introductionmentioning
confidence: 99%
“…The current in region-I follows a linear dependence, i.e., I  V and therefore, at low voltages (V < 0.45V) the ohmic transport is prevalent. The current varies almost linearly indicating that tunneling is the dominant charge transport mechanism at low voltage region [20,21]. In this region the number of injected electrons is very small and these are generated thermally, leading to very high electrical resistance.…”
Section: Electrical Characterization Of P-cuo/n-si Heterojunction Diodementioning
confidence: 96%
“…Hence, in the second region (0.45V <V <1.25V), the dominant transport mechanism is recombination-tunneling [20][21][22][23][24][25]. Finally, in region-III, the current follows a power law (I  V 2 ), indicating a space-charge limited current (SCLC) transport mechanism which is controlled by the presence of traps within the band gap of CuO [20][21][22][23][24][25]. The SCLC regime occurs when the equilibrium charge concentration is negligible compared to the injected charge concentration and this forms a space charge region near the injecting electrode.…”
Section: Electrical Characterization Of P-cuo/n-si Heterojunction Diodementioning
confidence: 98%
See 2 more Smart Citations